1974
DOI: 10.1084/jem.139.3.712
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Idiotypic Antibodies

Abstract: Individual antigenic determinants on antibodies were originally described by Kunkel et al. (1). Subsequently, the determinants, termed "idiotypes" by Oudin (2), have been described in antibody populations made in response to bacterial antigens (3) and to haptens (4). The antiidiotypic antisera are usually made in homologous or even heterologous species. Absorption of the antiidiotypic antisera with preinoculation serum or IgG from the individual whose idiotype is being studied might not remove antibodies speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

1975
1975
1992
1992

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(30 citation statements)
references
References 12 publications
(8 reference statements)
1
29
0
Order By: Relevance
“…Spleen and lymph node cells or purified lymphocytes from blood (Ficoll-Isopaque purified [1]) were used as responder cells and spleen cells as stimulator cells. Eagle's high amino acid medium (14) with the double amount of l-glutamine and complemented with penicillin, streptomycin, 0.5% (final dilution) of normal fresh BN rat serum, and 2.5 × 10 -5 M (final concentration) of 2-mercaptoethanol was used.…”
Section: Mixed Leukocyte Cultures (Mlc)mentioning
confidence: 99%
See 1 more Smart Citation
“…Spleen and lymph node cells or purified lymphocytes from blood (Ficoll-Isopaque purified [1]) were used as responder cells and spleen cells as stimulator cells. Eagle's high amino acid medium (14) with the double amount of l-glutamine and complemented with penicillin, streptomycin, 0.5% (final dilution) of normal fresh BN rat serum, and 2.5 × 10 -5 M (final concentration) of 2-mercaptoethanol was used.…”
Section: Mixed Leukocyte Cultures (Mlc)mentioning
confidence: 99%
“…One decisive factor in determining whether immune paralysis will occur or not is the concentration of the respective self-component in the body fluids. Here, it can be shown that the antigen-binding sites of the autochthonous immunoglobulin molecules under appropriate conditions can function as immunogens resulting in the production of auto-anti-idiotypic antibodies (1). In a few cases where difficulty has been encountered to achieve such auto-anti-idiotype antibody synthesis, this involved idiotypes being present in normal serum in unusually high concentrations (Janeway, Ch., Jr; personal communication).…”
mentioning
confidence: 99%
“…Though simultaneous complementary responses were induced intentionally and quite artifically in these experiments, the potential may exist in nature for other antigens and antibodies to stimulate comparable responses. Antibodies or antigen-antibody complexes can induce anti-idiotypic responses, and the inference is that complexes formed in vivo may account for induction of autogenous anti-idiotypic antibodies (22)(23)(24)(25)(26)(27)(28)(29)(30)(31). Also, preliminary studies in our laboratory suggest that some complex antigens may contain complementary determinants, each of which stimulates directly one of the complementary antibody responses (D. A. Rowley, unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
“…Discussion There is a growing body of evidence that anti-idiotypic antibodies can specifically regulate a number of immunological phenomena such as the suppression (11)(12)(13) or enhancement (14,15) of antibody production and the specific inhibition of graft-vs.-host (16,17) and mixed leukocyte culture reactivity (18). In most instances anti-idiotypic antibodies were raised by allo-(17) or heteroimmunization (14) though the production of autoanti-idiotypic antibodies has also been reported in rabbits (19). The data presented in this paper clearly demonstrate that anti-idiotypic antibodies raised syngeneically in strain 2 and 13 guinea pigs against anti-BPO-BGG can specifically and markedly suppress in vitro lympho- Table I. cyte proliferation of cells from syngeneic guinea pigs.…”
Section: Does the Interaction Of D Strain 2 And D Strain 13 Bpo-bgg Smentioning
confidence: 99%